IN SOCIAL-CULTURAL LIFE OF ANCIENT PEOPLE THE ROLE OF PHYSICAL EDUCATION AND SPORTS - Rakhmetov Takhir Tulaganovich (Proximus Journal Publishing, 2024)
The role and importance of physical education and sports in the formation of the young generation is studied in the article. Also, physical education and sports are considered as one of the main factors in raising the mature generation
Keywords: Physical culture; physical education and sports; adult generation; health